Simple stopping criterion for min-sum iterative decoding algorithm - Heo, J; Chung, K; Chugg, K M (Electronics letters, 2001)
A simple stopping criterion for iterative decoding based on min-sum processing is presented. While most stopping criteria suggested in the literature are based on cross entropy (CE) and its simplification, the proposed stopping criterion is to check whether a decoded sequence is a valid codeword along the encoder trellis structure. This new stopping criterion requires less computational complexity and saves memory.